2018
DOI: 10.1590/18069657rbcs20180025
|View full text |Cite
|
Sign up to set email alerts
|

Determining the In Situ Apparent Thermal Diffusivity of a Sandy Soil

Abstract: The thermal wave amplitude method is used to determine soil thermal diffusivity in situ for a sandy soil in Mexico (Coatzacoalcos, Veracruz). Soil diurnal temperature fluctuations were measured from depths of 0.05 to 0.65 m, in 0.01 m increments, during the months of April and August. Five mean diffusivity values were obtained experimentally, corresponding to the different depths combination. The soil thermal diffusivity ranged between 2.26 × 10-7 and 8.71 × 10-7 m 2 s-1. The diffusivity values obtained are wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Various efforts have concentrated on improving the packaging of sensors to ease data collection (Fanelli and Lautz, 2008;Gordon et al, 2013;Rau et al, 2010;Tonina et al, 2014), still without fundamentally overcoming other limitations. Recent developments, including custom vertically resolved probes linked to commercial (Aguilar et al, 2018;Andújar Márquez et al, 2016;Naranjo and Turcotte, 2015) or in-house loggers (Beardsmore et al, 2020;Léger et al, 2019), as well as some commercially available systems, are still limited in their vertical resolution, flexibility, and cost effectiveness for wide deployment. While fiber-optic-based methods have been widely applied for temperature measurement in deep wells, infrastructures, and streambeds (Briggs et al, 2012), their deployment for shallow and vertically resolved depth profiling of temperature is still challenging (Lundquist and Lott, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Various efforts have concentrated on improving the packaging of sensors to ease data collection (Fanelli and Lautz, 2008;Gordon et al, 2013;Rau et al, 2010;Tonina et al, 2014), still without fundamentally overcoming other limitations. Recent developments, including custom vertically resolved probes linked to commercial (Aguilar et al, 2018;Andújar Márquez et al, 2016;Naranjo and Turcotte, 2015) or in-house loggers (Beardsmore et al, 2020;Léger et al, 2019), as well as some commercially available systems, are still limited in their vertical resolution, flexibility, and cost effectiveness for wide deployment. While fiber-optic-based methods have been widely applied for temperature measurement in deep wells, infrastructures, and streambeds (Briggs et al, 2012), their deployment for shallow and vertically resolved depth profiling of temperature is still challenging (Lundquist and Lott, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Such pronounced peak values of α (0.83-0.99 mm 2 /s) were demonstrated for sandy soils at low water contents by Lebedev et al (2019). Silva-Aguilar et al (2018) reported that values of the apparent thermal diffusivity ranged between 0.23 and 0.87 mm 2 /s for sandy soils.…”
mentioning
confidence: 80%
“…Cable et al (2016) used this calibration approach to increase the accuracy of thermistors from 0.1ºC to approximately 0.02ºC for subsurface temperature measurements. While temperature-controlled water baths at temperatures above 0ºC (Aguilar et al, 2018;Naranjo and Turcotte, 2015) can be used for calibration using a reference thermometer, reaching an accuracy of 0.01ºC is challenging.…”
Section: Dtp Sensor Accuracy Assessment and Calibrationmentioning
confidence: 99%
“…Various efforts have concentrated on improving the packaging of sensors to ease data collection (Fanelli and Lautz, 2008;Gordon et al, 2013;Rau et al, 2010;Tonina et al, 2014), still without fundamentally overcoming other limitations. Recent developments, including custom vertically resolved probes linked to commercial (Aguilar et al, 2018;Andújar Márquez et al, 2016;Naranjo and Turcotte, 2015) or in-house loggers (Beardsmore et al, 2020;Léger et al, 2019), as well as some commercially available systems, are still limited in their vertical resolution, flexibility, and cost effectiveness for wide deployment. While fiber optic-based methods have been widely applied for temperature measurement in deep wells, infrastructures, and streambeds (Briggs et al, 2012), their deployment for numerous shallow and vertically resolved depth profiling of temperature is still challenging.…”
Section: Introductionmentioning
confidence: 99%